Efficacy and tolerability on melasma of a topical cosmetic product acting on melanocytes, fibroblasts and endothelial cells: a randomized comparative trial against 4% hydroquinone. (12th January 2020) - Bronzina, E.; Clement, A.; Marie, B.; Fook Chong, K.T.; Faure, P.; Passeron, T.
Abstract: Background: Recent data demonstrated that an altered basal membrane, activated melanocytes and secreted factors from keratinocytes but also fibroblasts and endothelial cells are involved in the pathophysiology of melasma. Objectives: To evaluate the efficacy and tolerability on melasma of a new topical skin‐lightening cosmetic product combination (CCP) targeting several factors identified to be involved in melasma pathogenesis compared to 4% hydroquinone (HQ). Methods: Forty‐three women with melasma were enrolled in a 12‐week double‐blind, randomized, parallel‐group trial and treated with CCP or 4% HQ cream. Efficacy was evaluated with the modified Melasma Area Severity Index (mMASI) score and colorimetric change. Cutaneous tolerability and patient satisfaction were also investigated. Results: The mMASI score decreased for both products from baseline and over the study period. At week 12, 90% of the subjects who received the combination products had an improvement in pigmentation vs. 79% with HQ. Similarly, both products significantly increased Individual Typological Angle parameters. For both measures, no statistically significant difference was observed between CCP and HQ in terms of change from baseline. CPP was very well tolerated. Conclusions: Cosmetic product combination is as effective as HQ in the management of facial dyspigmentation and represents a safe alternative.